Analytical study of hysterectomies - Neelgund, Shivaji; Hiremath, Panchaksharayya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Since early 20th century hysterectomy came into widespread use. The incidence of hysterectomy varies from place to place depending upon the clinical and clinician factors. Sometimes there are considerable problems in clinical assessments as the patient’s complaints, the clinical findings and per-operative diagnosis does not correlate with histopathological diagnosis. This is a retrospective study to correlate and evaluate the sensitivity between the indications, demographic features, clinical presentations, per-operative findings and histopathological diagnosis of patients who underwent hysterectomy. Methods: This study was conducted in the department of obstetrics and gynaecology, in SVMCH and RC, Ariyur, Pondicherry, India. There were 1124 cases of hysterectomies done over a period of five years, from 2011 to 2015. Data was recorded and analyzed from the case record of each patient, which was obtained from the medical record department of the hospital. Results: During the study period there were 1124 cases of hysterectomies done; out of which total abdominal hysterectomy with bilateral salphingo-oophorectomy were 915 cases 81.4%. Leiomyoma is the dominant histopathological diagnosis in our study 22.4%. Both adenomyosis and leiomyoma was present in 6.4% of the cases. In our study the pre-operative diagnosis, specificity to pathological correlation is 91 to 100%, and for leiomyoma it is 99%. Conclusions: Hysterectomy is the preferred procedure in the treatment for pelvic pathologies like fibroid, adenomyosis, pelvic inflammatory disease and malignant disorder, and genital prolapse. Majority of the hysterectomy procedures are performed via an abdominal approach.